A fire retardant coating for cable and preparation method thereof

By using a combination of flame retardant expansion agent and carbon nanotubes in cable fire retardant coatings, the problems of low fire stability and short fire resistance time of existing fire retardant coatings are solved, and higher fire resistance stability and longer flame retardant time are achieved.

CN116948452BActive Publication Date: 2025-03-07刘金宏
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311073270.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-03-07
Estimated Expiration
2043-08-24

AI Technical Summary

Technical Problem

The existing inflatable fireproof and heat-proof coatings have low fire resistance and short fire resistance time.

Method used

A cable fire-retardant coating is used, which includes 10 to 20 parts of flame retardant type expansion agent and 1 to 3 parts of carbon nanotubes. The flame retardant type expansion agent is composed of ammonium polyphosphate, melamine foam sponge, small-particle starch and ferrous disulfide, and the net structure stability of the flame retardant type expansion agent is enhanced by carbon nanotubes.

Benefits of technology

It improves the fire resistance stability and sustainability of the outer fireproof coating of cable, extends the flame retardant time, and enhances the flame retardant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004411886290000071
    Figure BDA0004411886290000071
  • Figure BDA0004411886290000081
    Figure BDA0004411886290000081
Patent Text Reader

Abstract

The present application relates to the field of fire retardant coatings, and specifically discloses a cable fire retardant coating and a preparation method thereof. A cable fire retardant coating comprises 10 to 20 parts of a flame retardant expansion agent and 1 to 3 parts of carbon nanotubes; the flame retardant expansion agent comprises 5 to 10 parts of ammonium polyphosphate, 2 to 5 parts of melamine foam sponges, 4 to 7 parts of small-particle starch, 2 to 4 parts of ferrous disulfide and water. The preparation method thereof is as follows: mixing small-particle starch with water to obtain a paste of small-particle starch; mixing ammonium polyphosphate, melamine foam sponge, paste of small-particle starch, ferrous disulfide and water to obtain a flame retardant expansion agent; mixing the flame retardant expansion agent with carbon nanotubes to obtain a cable fire retardant coating. The cable fire retardant coating of the present application has the advantages of expanding and reacting at high temperatures, and blocking external oxygen and fire sources for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fire retardant coatings, and more specifically, to a cable fire retardant coating and a preparation method thereof. Background Art

[0002] Cables are widely used to transmit electricity from power plants to cities, industrial parks or residential areas. They carry high voltage and large current, but damage to cable insulation can cause short circuits and fires. In order to avoid the expansion and spread of cable fires, and to avoid external fires causing cable fires, cable surfaces are usually coated with cable fire-retardant coatings.

[0003] The patent with application number CN116285523A provides an intumescent fireproof and heat-insulating coating. The raw materials for preparing the intumescent fireproof and heat-insulating coating are: 20 to 40 parts of coating matrix, 10 to 30 parts of catalyst, 1 to 10 parts of carbonizing agent, 1 to 10 parts of foaming agent, 5 to 15 parts of filler, 0.1 to 2 parts of auxiliary agent or 10 to 30 parts of water; the coating matrix includes at least one of water-based epoxy emulsion, polyvinyl acetate-ethylene copolymer emulsion, self-crosslinking silicone-acrylic emulsion, acrylate emulsion, styrene-acrylic emulsion or acetate-acrylic emulsion; the carbonizing agent includes at least one of pentaerythritol, dipentaerythritol, tripentaerythritol, starch, cellulose and derivatives, sucrose, and sorbitol, and the foaming agent is at least one of urea, dicyandiamide, melamine, and melamine urate. The preparation steps are as follows: the catalyst, carbon former, foaming agent, filler, additive and water are mixed by weight, stirred, ball-milled, and filtered to obtain slurry, the slurry is mixed with the coating matrix, and then filtered to obtain the intumescent fireproof and heat-insulating coating.

[0004] The above-mentioned intumescent fireproof and heat-insulating coating is simply a mixture of various raw materials, and has the disadvantages of low fireproof stability and short fireproof time of the cable fireproof coating. Summary of the invention

[0005] In order to solve the shortcomings of existing intumescent fire-retardant and heat-insulating coatings, such as low fire-retardant stability and long fire-retardant time, the present application provides a cable fire-retardant coating and a preparation method thereof.

[0006] In the first aspect, the present application provides a cable fire retardant coating, which adopts the following technical solution:

[0007] A cable fire retardant coating comprises the following raw materials in parts by weight: 10 to 20 parts of a flame retardant expansion agent and 1 to 3 parts of carbon nanotubes; the flame retardant expansion agent comprises 5 to 10 parts of ammonium polyphosphate, 2 to 5 parts of melamine foam sponge, 4 to 7 parts of small-particle starch, 2 to 4 parts of ferrous disulfide and water, wherein the ammonium polyphosphate, melamine foam sponge, ferrous disulfide and small-particle starch are all based on the weight of the flame retardant expansion agent.

[0008] By adopting the above technical scheme, the flame retardant expansion agent and the carbon nanotubes are mixed. While the carbon nanotubes exert their own high temperature resistance, the network structure stability of the flame retardant expansion agent is enhanced, so that the thickness of the cable fire retardant coating layer on the outer layer of the cable is difficult to change, the cable has strong flame retardancy, a long flame retardant time and a good flame retardant effect; melamine itself has a good flame retardant effect, ferrous disulfide is filled in the pores of the melamine foam sponge, when encountering a fire, when the internal temperature of the flame retardant expansion agent rises, the ferrous disulfide will react with the oxygen inside the melamine foam sponge to generate sulfur dioxide and sulfur trioxide, sulfur dioxide and sulfur trioxide are both non-flammable in the air, and the flame retardant expansion agent is almost isolated from oxygen, preventing the fire from spreading; small-particle starch is filled in the melamine foam sponge, and when the ammonium polyphosphate is preheated and decomposed to form a strong dehydrating agent, the small-particle starch is carbonized and expanded, filling the pores inside the ferrous disulfide foam sponge, so that the expansion flame retardant has high stability after expansion and a long flame retardant time.

[0009] Optionally, the mass ratio of the ammonium polyphosphate, melamine foam sponge, small-particle starch and ferrous disulfide is (6-8):5:5:2.

[0010] By adopting the above technical scheme, suitable proportions of ammonium polyphosphate, melamine foam sponge, ferrous disulfide and small-particle starch can make the small-particle starch and ferrous disulfide just evenly fill and cover the surface of the internal pores of the melamine foam sponge, and the dehydrating agent formed after the decomposition of ammonium polyphosphate can also properly carbonize the small-particle starch. The cable fire retardant coating finally obtained has high fire stability and good fire resistance sustainability.

[0011] Optionally, the particle size of the small-particle starch is 5 to 30 μm.

[0012] By adopting the above technical scheme, small-particle starch with a particle size of 5 to 30 μm can be fully filled and dispersed on the surface of the pores of the melamine foam sponge, so that the small-particle starch has better expansion uniformity after carbonization and the cable fire retardant coating on the entire cable surface has better flame retardant uniformity.

[0013] Optionally, the small particle size starch is high amylose starch.

[0014] By adopting the above technical solution, the particle size of high-amylose starch is smaller, and it has more branches, and it is round particles with a large specific surface area and a fast carbonization speed, which improves the fireproof speed of the cable fire retardant coating and allows the cable to be quickly isolated from the fire source.

[0015] Optionally, the particle size of the melamine foam sponge is 0.5-2 mm.

[0016] By adopting the above technical scheme, the cable fire retardant coating prepared by the melamine foam sponge with suitable particle size can be evenly applied to the cable surface without the problem of particles being too large to collide and fall off or particles being too small to play the role of a skeleton. The prepared cable fire retardant coating has good fireproof stability and a long fireproof time.

[0017] Optionally, the carbon nanotubes are liquid carbon nanotubes.

[0018] By adopting the above technical scheme, liquid carbon nanotubes can be fully mixed with other raw materials, and can flow freely in the pores of melamine foam sponge. While being fully mixed with other raw materials and acting as a high temperature resistant material, they cooperate with melamine foam sponge as a skeleton after the expansion of other raw materials. The obtained cable fire retardant coating has good fire resistance stability and a long fire resistance time.

[0019] In a second aspect, the present application provides a method for preparing a cable fire retardant coating, using the following technical solution:

[0020] A method for preparing a cable fire retardant coating comprises the following steps: mixing a flame retardant expansion agent with carbon nanotubes and stirring for 30 to 60 minutes to obtain the cable fire retardant coating.

[0021] By adopting the above technical scheme, the flame retardant expansion agent and the carbon nanotubes are mixed and stirred, so that the carbon nanotubes are fully filled in the interior of the flame retardant expansion agent, and cooperate with the melamine foam sponge in the flame retardant expansion agent to play a skeleton role. The prepared cable fire retardant coating has good fire resistance stability and a long fire resistance time.

[0022] Optionally, the preparation method of the flame retardant expansion agent is as follows:

[0023] Step 1, mixing small-particle starch with water to obtain paste-like small-particle starch;

[0024] Step 2, mixing ammonium polyphosphate, melamine foam sponge, paste-like small-particle starch, ferrous disulfide and water, wherein the volume of the water is equal to the volume of the melamine foam sponge, to obtain a diluted flame-retardant expansion agent.

[0025] By adopting the above technical scheme, small-size starch is first prepared into a paste of small-size starch, so that the paste of small-size starch is fully and evenly filled in the pores inside the melamine foam sponge. The prepared cable fire retardant coating has a uniform thickness after expansion, high fireproof stability and good fireproof effect.

[0026] Optionally, in step 2, ammonium polyphosphate, melamine foam sponge, paste-like small-particle starch, ferrous disulfide and water are mixed and stirred under heating conditions until 50% v / v of the water is volatilized to obtain a flame-retardant expansion agent.

[0027] By adopting the above technical scheme, after 50% v / v of water equal to the volume of the melamine foam sponge is volatilized, ammonium polyphosphate, paste-like small-size starch particles, and ferrous disulfide will just adhere to the pores of the melamine foam sponge, so that the ammonium polyphosphate, paste-like small-size starch particles, and ferrous disulfide will adhere to the melamine foam sponge to be evenly distributed without settling due to gravity, and the flame-retardant expansion agent after carbonization expansion has a uniform thickness, good flame-retardant effect, and a long flame-retardant time.

[0028] Optionally, in step 2, the heating temperature condition is 50-65°C.

[0029] By adopting the above technical scheme, under this temperature condition, ammonium polyphosphate, paste-like small-particle starch and ferrous disulfide will not be too dry or wet, and will be firmly attached to the melamine foam sponge. The carbonized flame-retardant expansion agent will expand to a uniform and appropriate thickness, with good flame-retardant effect and long flame-retardant time.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. In the present application, melamine itself has a good flame retardant effect. Ferrous disulfide is filled in the pores of the melamine foam sponge. When a fire occurs and the internal temperature of the flame retardant expansion agent rises, the ferrous disulfide will react with the oxygen inside the melamine foam sponge to generate sulfur dioxide and sulfur trioxide. Both sulfur dioxide and sulfur trioxide are non-flammable in the air, and the flame retardant expansion agent is almost isolated from oxygen to prevent the spread of fire; small-sized starch is filled in the melamine foam sponge. When the ammonium polyphosphate is preheated and decomposed to form a strong dehydrating agent, the small-sized starch is carbonized and expanded to fill the pores inside the ferrous disulfide foam sponge, so that the cable fire retardant coating has high stability after expansion and a long flame retardant time;

[0032] 2. In the present application, the flame retardant expansion agent and the carbon nanotubes are mixed. The carbon nanotubes are resistant to high temperatures and enhance the stability of the network structure of the flame retardant expansion agent, so that the thickness of the cable fire retardant coating on the outer layer of the cable is difficult to change. The cable has strong flame retardancy, a long flame retardant time and a good flame retardant effect.

[0033] 3. In the preparation steps of the present application, the small-particle starch is first prepared into a paste of small-particle starch, so that the paste of small-particle starch is fully and evenly filled in the pores inside the melamine foam sponge, so that the thickness of the cable fire retardant coating after expansion is uniform, the fireproof stability is high, and the fireproof effect is good. DETAILED DESCRIPTION

[0034] The raw materials of the examples and comparative examples of the present application can all be purchased commercially.

[0035] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0036] Example

[0037] Example 1

[0038] Preparation of flame retardant expansion agent:

[0039] Step 1, mixing 4 g of high-amylose corn starch with a particle size of 10 to 30 μm with 4 g of water, and stirring at a speed of 500 rpm for 30 min to obtain a paste-like small-particle starch;

[0040] Step 2, 5g of ammonium polyphosphate, 5g of melamine foam sponge with a particle size of 0.5-2mm, the paste-like small-particle starch obtained in step 1, 2g of ferrous disulfide and 15g of water are mixed under heating conditions of 50°C, and stirred at a speed of 300rpm until 50% v / v of the water is volatilized to obtain a flame retardant expansion agent.

[0041] Preparation of cable fire retardant coating:

[0042] 20 g of the flame retardant expansion agent prepared above and 5 g of carbon nanotubes were mixed and stirred at a speed of 500 rpm for 30 minutes to obtain a liquid cable fire retardant coating.

[0043] Pour the cable fire retardant coating into the PVC pipe extrusion mold, then put the mold into an oven, dry it at 50℃ for 2h, cool it to 25℃, and demold it to get the formed cable fire retardant coating.

[0044] Example 2

[0045] Preparation of flame retardant expansion agent:

[0046] Step 1, mixing 7 g of high-amylose corn starch with a particle size of 10 to 30 μm with 7 g of water, and stirring at a speed of 500 rpm for 30 min to obtain a paste-like small-particle starch;

[0047] Step 2, 10g of ammonium polyphosphate, 2g of melamine foam sponge with a particle size of 0.5-2mm, the paste-like small-particle starch obtained in step 1, 4g of ferrous disulfide and 20g of water are mixed under heating conditions of 65°C, and stirred at a speed of 300rpm until 50% v / v of the water is volatilized to obtain a flame retardant expansion agent.

[0048] Preparation of cable fire retardant coating:

[0049] 40 g of the flame retardant expansion agent prepared above and 3 g of carbon nanotubes were mixed and stirred at a speed of 500 rpm for 60 minutes to obtain a liquid cable fire retardant coating.

[0050] Pour the cable fire retardant coating into the PVC pipe extrusion mold, then put the mold into an oven, dry it at 50℃ for 2h, cool it to 25℃, and demold it to get the formed cable fire retardant coating.

[0051] Example 3

[0052] Preparation of flame retardant expansion agent:

[0053] Step 1, mixing 5 g of high-amylose corn starch with a particle size of 10 to 30 μm with 5 g of water, and stirring at a speed of 500 rpm for 30 min to obtain a paste-like small-particle starch;

[0054] Step 2, 7g of ammonium polyphosphate, 4g of melamine foam sponge with a particle size of 0.5-2mm, the paste-like small-particle starch obtained in step 1, 3g of ferrous disulfide and 17g of water are mixed under heating conditions of 58°C, and stirred at a speed of 300rpm until 50% v / v of the water is volatilized to obtain a flame retardant expansion agent.

[0055] Preparation of cable fire retardant coating:

[0056] 30 g of the flame retardant expansion agent prepared above and 4 g of carbon nanotubes were mixed and stirred at a speed of 500 rpm for 45 minutes to obtain a liquid cable fire retardant coating.

[0057] Pour the cable fire retardant coating into the PVC pipe extrusion mold, then put the mold into an oven, dry it at 50℃ for 2h, cool it to 25℃, and demold it to get the formed cable fire retardant coating.

[0058] Example 4

[0059] The difference from Example 3 is that the total mass of ammonium polyphosphate, melamine foam sponge, small-particle starch and ferrous disulfide remains unchanged, and the mass ratio of ammonium polyphosphate, melamine foam sponge, small-particle starch and ferrous disulfide is 7:5:5:2; the specific steps are as follows:

[0060] Preparation of flame retardant expansion agent:

[0061] Step 1, mixing 4 g of high-amylose corn starch with a particle size of 10 to 30 μm with 4 g of water, and stirring at a speed of 500 rpm for 30 min to obtain a paste-like small-particle starch;

[0062] Step 2, 7g of ammonium polyphosphate, 4g of melamine foam sponge with a particle size of 0.5-2mm, the paste-like small-particle starch obtained in step 1, 2g of ferrous disulfide and 15g of water are mixed under heating conditions of 50°C, and stirred at a speed of 300rpm until 50% v / v of the water is volatilized to obtain a flame retardant expansion agent.

[0063] Preparation of cable fire retardant coating:

[0064] 30 g of the flame retardant expansion agent prepared above and 4 g of carbon nanotubes were mixed and stirred at a speed of 500 rpm for 45 minutes to obtain a liquid cable fire retardant coating.

[0065] Pour the cable fire retardant coating into the PVC pipe extrusion mold, then put the mold into an oven, dry it at 50℃ for 2h, cool it to 25℃, and demold it to get the formed cable fire retardant coating.

[0066] Example 5

[0067] The difference from Example 4 is that the preparation steps of the flame retardant expansion agent are different, and the specific steps are as follows:

[0068] Preparation of flame retardant expansion agent:

[0069] 4 g of high-amylose corn starch with a particle size of 10 to 30 μm, 7 g of ammonium polyphosphate, 4 g of melamine foam sponge with a particle size of 0.5 to 2 mm, 2 g of ferrous disulfide and 19 g of water are mixed under heating conditions of 50° C., and then stirred at a speed of 300 rpm until 50% v / v of the water is evaporated to obtain a flame retardant expansion agent.

[0070] Example 6

[0071] The difference from Example 4 is that the preparation steps of the flame retardant expansion agent are different, and the water evaporation step is not performed in step 2. The specific steps are as follows:

[0072] Preparation of flame retardant expansion agent:

[0073] Step 1, mixing 4 g of high-amylose corn starch with a particle size of 10 to 30 μm with 4 g of water, and stirring at a speed of 500 rpm for 30 min to obtain a paste-like small-particle starch;

[0074] Step 2, 7g of ammonium polyphosphate, 4g of melamine foam sponge with a particle size of 0.5-2mm, the paste-like small-particle starch obtained in step 1, 2g of ferrous disulfide and 15g of water are mixed under heating conditions of 50°C, and stirred at a speed of 300rpm for 10min to obtain a flame retardant expansion agent.

[0075] Example 7

[0076] The difference from Example 4 is that the preparation steps of the flame retardant expansion agent are different, and the heating temperature in step 2 is different. The specific steps are as follows:

[0077] Preparation of flame retardant expansion agent:

[0078] Step 1, mixing 4 g of high-amylose corn starch with a particle size of 10 to 30 μm with 4 g of water, and stirring at a speed of 500 rpm for 30 min to obtain a paste-like small-particle starch;

[0079] Step 2, 7g of ammonium polyphosphate, 4g of melamine foam sponge with a particle size of 0.5-2mm, the paste-like small-particle starch obtained in step 1, 2g of ferrous disulfide and 15g of water are mixed under heating conditions of 100°C, and stirred at a speed of 300rpm until 50% v / v of the water is volatilized to obtain a flame retardant expansion agent.

[0080] Comparative Example

[0081] Comparative Example 1

[0082] The difference from Example 4 is that no carbon nanotubes are added to the cable fire retardant coating.

[0083] Comparative Example 2

[0084] The difference from Example 4 is that ammonium polyphosphate is not added to the flame retardant expansion agent.

[0085] Comparative Example 3

[0086] The difference from Example 4 is that the melamine foam sponge in step 2 of the preparation of the flame retardant expansion agent is replaced by an equal weight of melamine powder.

[0087] Comparative Example 4

[0088] The difference from Example 4 is that the high-amylose corn starch in step 1 in the preparation of the flame retardant expansion agent is replaced with an equal weight of low-amylose corn starch.

[0089] Comparative Example 5

[0090] The difference from Example 4 is that no ferrous disulfide is added to the flame retardant expansion agent.

[0091] Performance testing

[0092] Testing method Testing items: Using the cable fire retardant coatings prepared in the above embodiments and comparative examples to test the limiting oxygen index and UL94 vertical burning grade;

[0093] (1) Limiting oxygen index is referred to as LOI. It is used to judge the difficulty of burning materials based on the oxygen index. When the oxygen index exceeds a certain value, the material is considered difficult to burn. When it is lower than a certain value, it is considered flammable. There are usually the following classifications:

[0094] 1. LOI < 22% is flammable;

[0095] 2. LOI between 22% and 27% is flammable;

[0096] 3. LOI between 27% and 34% is considered flame retardant;

[0097] 4. LOI>34% is non-flammable;

[0098] The GB / T2408-2008 test standard was adopted and the limiting oxygen index instrument of the Swedish Nordic Scientifc company was used for testing. The sample size used was 200mm×400mm×800mm, with 6 samples in each group, and the average value was taken for statistics.

[0099] (2) UL94 vertical combustion The samples were tested using the UL test method and the GB / T 5169.17-2008 test standard. Six samples were tested in each group. The combustion classification is shown in Table 1:

[0100] Table 1

[0101]

[0102] The detection limit oxygen index and UL94 vertical combustion grade of the cable fire retardant coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 5 are shown in Table 2 below:

[0103] Table 2

[0104]

[0105] Combining the data of Examples 1, 2, and 3, it can be seen that the only difference between Examples 1, 2, and 3 is the different raw material composition ratios. The cable fire retardant coating prepared in Example 3 has the highest limiting oxygen index, and the UL94 vertical burning grade is also V-0, which is the highest flame retardant grade. Therefore, the raw material composition of Example 3 is the best ratio.

[0106] In Example 4, the mass ratio of ammonium polyphosphate, melamine foam sponge, small-particle starch and ferrous disulfide is 7:5:5:2. The limiting oxygen index of the cable fire retardant coating prepared in Example 4 is higher than that in Example 3, and the UL94 vertical burning grade is also V-0, which is the highest flame retardant grade. Therefore, the mass ratio of ammonium polyphosphate, melamine foam sponge, small-particle starch and ferrous disulfide is extremely important. Example 4 is the optimal ratio of ammonium polyphosphate, melamine foam sponge, small-particle starch and ferrous disulfide.

[0107] In the preparation steps of Example 5, step 1 and step 2 for preparing the flame retardant expansion agent are not carried out separately, and the raw materials for preparing the flame retardant expansion agent are added into water and stirred at the same time. The limiting oxygen index of the obtained cable fire retardant coating is lower than that of Example 4, and the UL94 vertical burning grade is V-1, which is also lower than that of Example 4, which proves that the step of preparing the flame retardant expansion agent is extremely important.

[0108] In the preparation steps of Example 6, in step 2 of preparing the flame retardant expansion agent, the step of water volatilization is not performed, and the obtained cable fire retardant coating has a limiting oxygen index lower than that of Example 4, and a UL94 vertical burning grade of V-1, which is also lower than that of Example 4, proving that the step of water volatilization is extremely important in the preparation of the flame retardant expansion agent.

[0109] In the preparation steps of Example 7, in step 2 of preparing the flame retardant expansion agent, water is volatilized at 100°C, and the obtained cable fire retardant coating has a limiting oxygen index lower than that of Example 4, and a UL94 vertical burning grade of V-1, which is also lower than that of Example 4, proving that the water volatilization temperature is extremely important in the preparation of the flame retardant expansion agent.

[0110] In Comparative Example 1, no carbon nanotubes are added, and the obtained cable fire retardant coating has a limiting oxygen index lower than all the embodiments, and a UL94 vertical burning grade of V-2, which proves that the addition of carbon nanotubes is indispensable in the cable fire retardant coating of the present application.

[0111] In Comparative Examples 2 and 5, no ammonium polyphosphate and ferrous disulfide are added respectively. The cable fire retardant coatings prepared in Comparative Examples 2 and 5 have a low limiting oxygen index and a UL94 vertical combustion grade of V-2, which is far worse than the effects of the cable fire retardant coatings prepared in all embodiments. This proves that ammonium polyphosphate and ferrous disulfide are indispensable in the cable fire retardant coatings.

[0112] In Comparative Example 3, the melamine foam sponge was replaced with an equal weight of melamine powder. The resulting cable fire retardant coating had a low limiting oxygen index and a UL94 vertical burning rating of V-2, which was far inferior to the effects of the cable fire retardant coatings obtained in all the embodiments, proving that the melamine foam sponge cannot be replaced by melamine powder.

[0113] In Comparative Example 4, high-amylose corn starch was replaced with low-amylose corn starch of equal mass, and the resulting cable fire retardant coating had a low limiting oxygen index and a UL94 vertical burning rating of V-2, which was far worse than that of the cable fire retardant coatings obtained in all the embodiments, proving that the high-amylose corn starch in this application cannot be replaced by low-amylose corn starch.

[0114] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A cable fire retardant coating, characterized in that: The invention comprises the following raw materials in parts by weight: 10 to 20 parts of a flame retardant expansion agent and 1 to 3 parts of carbon nanotubes; the flame retardant expansion agent comprises 5 to 10 parts of ammonium polyphosphate, 2 to 5 parts of melamine foam sponge, 4 to 7 parts of small-particle starch, 2 to 4 parts of ferrous disulfide and water, wherein the weight parts of ammonium polyphosphate, melamine foam sponge, ferrous disulfide and small-particle starch are all based on the weight parts of the flame retardant expansion agent; the particle size of the small-particle starch is 5 to 30 μm; and the small-particle starch is high-amylose starch.

2. A cable fire retardant coating according to claim 1, characterized in that The mass ratio of the ammonium polyphosphate, melamine foam sponge, small-particle starch and ferrous disulfide is (6-8):5:5:

2.

3. The cable fire retardant coating according to claim 1, characterized in that: The particle size of the melamine foam sponge is 0.5-2 mm.

4. The cable fire retardant coating according to claim 1, characterized in that: The carbon nanotubes are liquid carbon nanotubes.

5. A method for preparing a cable fire retardant coating as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: The flame retardant expansion agent and the carbon nanotubes are mixed and stirred for 30 to 60 minutes to obtain a cable fire retardant coating.

6. The method for preparing a cable fire retardant coating according to claim 5, characterized in that: The preparation method of the flame retardant expansion agent is as follows: Step 1, mixing small-particle starch with water to obtain paste-like small-particle starch; Step 2, mixing ammonium polyphosphate, melamine foam sponge, paste-like small-particle starch, ferrous disulfide and water, wherein the volume of the water is equal to the volume of the melamine foam sponge, to obtain a diluted flame-retardant expansion agent.

7. The method for preparing a cable fire retardant coating according to claim 6, characterized in that: In the step 2, ammonium polyphosphate, melamine foam sponge, paste-like small-size starch, ferrous disulfide and water are mixed and stirred under heating conditions until 50% v / v of the water is volatilized to obtain a flame retardant expansion agent.

8. The method for preparing a cable fire retardant coating according to claim 7, characterized in that: In the step 2, the heating temperature is 50-65°C.

Citation Information

Patent Citations

  • Intumescent fireproof heat-insulating coating and application thereof

    CN116285523A

  • Expansion-type fireproof coating

    CN103351815A

  • High-flame-retardant low-smoke-toxicity weather-resistant electric cable sheath material and preparation method thereof

    CN110591335A